First report of grapevine red blotch virus infecting grapevine in Argentina - Luna, Facundo; Debat, Humberto Julio; Moyano, Sabrina Noé; Zavallo, Diego; Asurmendi, Sebastian; Gomez Talquenca, Gonzalo (Springer, 2019)
Argentina is the fifth wine producer worldwide and 10th global grapevine producer, with over 2,100,000 tons of grapes harvested in 2017. So far, 12 viruses have been identified in grapevine in Argentina (Debat et al. 2019).